Analytical study on the viability of adaptive reuse with social approach. Case study of Asia Heritage Row, Kuala Lumpur - Basha, Brunilda; Soomro, Ali Raza; Abdullah, Fadzidah (2016)
Nowadays in the process of conservation, Adaptive Reuse Practice has been necessary. It holds different dimensions of sustainability that of; economical, environmental and social. In the pursuit of the sustainable development, social sustainability has been the new parameter to investigate the viability of adaptive reuse. Asia Heritage Row located in Doraisami Street and Jalan Yap Ah Shak, Kuala Lumpur is used for the hypothesis testing. The variables that are measured as parameters in achieving social sustainability are categorized into cultural, aesthetical, social and human comfort. This study aims to study the viability of adaptive reuse of the Asia Heritage Row towards social sustainability of heritage built environment in Kuala Lumpur. The data is mainly collected from literature review, case study and questionnaires.The data is analyzed by determining the statically reliable relationship between adaptive reuse and social sustainability parameters.